2010
DOI: 10.1007/bf03246184
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel preparation and characterization of Co/TiO2 nanoparticles: Application to the degradation of methyl orange

Abstract: Cobalt doped titania nanoparticles were synthesized by sol-gel method using titanium(IV) isopropoxide and cobalt nitrate as precursors. X-Ray diffraction (XRD) results showed that titania and Co/TiO 2 nanoparticles only include anatase phase. The framework substitution of Co in TiO 2 nanoparticles was established by XRD, scanning electron microscopy equipped with energy dispersive X-ray microanalysis (SEM-EDX) and Fourier transform infrared (FT-IR) techniques. Transmission electron microscopy (TEM) images conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(69 citation statements)
references
References 34 publications
(40 reference statements)
7
62
0
Order By: Relevance
“…3 at 0.6, 6.9 and 7.5 keV. The less intense peak is assigned to cobalt in the TiO 2 lattices [20,38]. These results confirmed the existence of cobalt atoms in the Co/TiO 2 samples but the XRD patterns do not show any diffractions related to cobalt.…”
Section: Sem/edx Analysissupporting
confidence: 59%
See 1 more Smart Citation
“…3 at 0.6, 6.9 and 7.5 keV. The less intense peak is assigned to cobalt in the TiO 2 lattices [20,38]. These results confirmed the existence of cobalt atoms in the Co/TiO 2 samples but the XRD patterns do not show any diffractions related to cobalt.…”
Section: Sem/edx Analysissupporting
confidence: 59%
“…In the case of Co/TiO 2 (d) sample, it can be concluded that the addition of cobalt to titania hinders the growth of TiO 2 nanoparticles. It seems that cobalt ions form complex with the TiO 2 surface oxygen, hence, suppress the growth of TiO 2 crystallite [38].…”
Section: Xrd Analysismentioning
confidence: 99%
“…6b), [35]. When the concentration TiO 2 increases, these peaks appear again, but supplementary peaks appear at 2θ= 46…”
Section: = 16mentioning
confidence: 90%
“…With increase of Eu concentration from 1 mol% to 5 mol% the surface hydroxyl groups in the host (CaF 2 ) lattice are said to increase [10]. The increase in number of hydroxyl groups increase the intensity of FTIR absorption bands.…”
Section: Pxrd Sem and Ftirmentioning
confidence: 99%